The occupant's satisfaction on quality work of service providers appointed by management corporation / Nurul Ashikin Mat Sori and Siti Nadiah Mhd Ali - Mat Sori, Nurul Ashikin; Mhd Ali, Siti Nadiah (2018)
It is important to know the level of the occupant's satisfaction with quality of work from service provider as it is related to the occupant's comfort with the services provided by the apartment. The quality of work from service providers can determine the satisfaction of an occupant. The objective of this research is to rank the level of satisfaction towards the services provided by the service providers and to determine the level of the occupant's satisfaction with quality of work from service providers appointed by the Management Corporation. This research uses the quantitative method and data have been collected by using questionnaires in order to achieve the objectives of the research. The questionnaires were distributed among the occupants of D' Perdana Apartment Sri Cemerlang Kota Bharu Kelantan. Data was analyzed using Statistical Package for Social Sciences (SPSS) and Microsoft Excel to know the results. At the end of the research, the result shows the satisfaction level of the occupants on quality of work of the service providers is good. The occupants live comfortably and get good quality of service at the apartment. The service providers have to ensure the occupants are always satisfied with their service and fulfill the needs of occupants related to the service.